Does Empathy Offer a Good Alternative to the Concept of Self-Love In Kant and Nietzsche’s Views? A Reply to Saunders - Allan Arturo Gonzalez Estrada (Public Reason)
Recent discussions on the views of self-love in Kant and Nietzsche (Owen 2017, 2019; Saunders, 2023) suggest a conflict between this concept and our duties to others and, how we should pursue and implement such responsibilities at individual and social level. If Kant is correct, our self-love should be subordinated to the moral law or practical reason; otherwise, self-love could influence the will and compromise free choice. On the other hand, as Owen has pointed out, Nietzsche offers an alternative approach to channelling self-love. In this Nietzschean view, self-love becomes the cornerstone of our moral and social development. Saunders argues that empathy, as a third alternative, can help us escape this dichotomy. However, I contend that empathy, while important, is not sufficient, as it may be a fleeting emotion that fails to convey dignity and respect to others. I will argue that a Nietzschean perspective on self-love, combined with Kant’s doctrine of virtues, helps us understand the current debate. My view is that if a bridge, between the Duties of Love and the Duties of Virtue toward other human beings in a Kantian framework with the channelling strategy of Nietzsche can be created, then we can keep the concepts of dignity and respect and over empathy. Once this bridge is established, the Duties of Virtue toward other human beings can effectively be utilized to pursue personal and collective development within the Nietzschean position, this approach aligns with a political and ethical view aimed at elevating morality via dignity and respect to the highest possible virtue for all.